Frações físicas e qualidade da matéria orgânica em agroecossistemas do Bioma Pampa. - Santos, Daiane Carvalho dos (2011)
Few studies evaluate the dynamics and quality of soil organic matter (OM) in agroecosystems of the Pampa Biome. Conservation tillage systems based on the reduction of tillage operations and addition of crop residues, contribute to maintaining and improving soil quality and the environment. In this work, the studies 1 and 2 are related to evaluation of physical fractions of organic matter from the point of view of quantity and quality in the whole soil and in aggregates under areas arenizadas in the southwest of RS, This studies was done in an Paleudult under cultivation of eucalyptus forest homogeneous (FH) system agrosilvopasture (SA) and native (CN). The studies 3 and 4 aimed evaluating quantitatively and qualitatively the physical fractions of organic matter in whole soil and in aggregate in an Albaqualf under cultivation of ryegrass (Lollium multiflorum Lam) + birdsfoot trefoil (Lotus corniculatus), as cover crops in winter and rotation soybean (Glycine max L.) / maize (Zea mays L.) / sorghum (Sorghum vulgare) in the summer in conventional tillage (CT) and no-tillage (NT). As reference area, was sampled an native area (CN). For both studies, soil was collected in the layers from 0.000 to 0.025m and 0.025 to 0.075m depth. The soil was air-dried and sieved at 8.00mm mesh and in aggregate classes (8.00 to 4.76, 4.76 - 2.00, 2.00 to 1.00, 1.00 to 0.50, 0.50 to 0.25 and <0.25mm). The stocks were determined from total organic carbon (TOC) in layers from 0.000 to 0.025m and 0.025 to 0.075m. The physical fractionation and granulometric densimetric SOM were realized to obtain the coarse fraction (CGC), carbon associated with minerals (CAM), free light fraction (FLF), occluded light fraction (OLF) and heavy fraction (HF). The first one study it was concluded that cultivation of FH in sandy soils caused increase in the stock of TOC, total nitrogen (TN) in the soil and fractions CFG, CAM, FLF and OLF when compared to CN in the surface layer. The SA in the soil samples showed more humified OM compared to CN and FH. The OLF, physically protected within the soil aggregates, presented higher proportion of more recalcitrant compounds in relation to FLF. In study 2 concluded that the FH showed the highest values of TOC accumulated in the layer from 0.000 to 0.075m depth in classes of 8.00 to 1.00mm and for the CFG and CAM in theclasses 8.00 to 0,50mm. The FLF was sensitive to changes in land use in the aggregates from 8.00 to 4.76mm at depths from 0.000 to 0.025m 0.025 to 0.075m, and these increments to the FH and CN, respectively. For all systems evaluated (FH, SA and CN), the degree of humification was higher in smaller diameter classes (0.50 - <0.25mm). The OLF showed higher free radical semiquinone, indicating humification. It was concluded from the study 3 that the NT in lowland soils increases the stock of CFG and FLF in comparison to the CT. This effect was restricted to the superficial layer, and these fractions were more sensitive than the TOC to changes in land management. In four years of experiment, te management systems had no effect on the stock of CAM and HF. By Laser Induced Fluorescence (LIF), under CT soil samples showed humified OM compared to the NT and CN. The FLF had a higher proportion of more labile compounds in relation to the OLF. In the study 4 it was concluded that the management systems under CT and NT in lowlands, reduced TOC, FLF and OLF in the aggregates of 4.76 to <0.25mm and a CFG in the classes 12 of 2.00 to <0.25mm compared to CN. Increases in stock of the FLF under NT were obtained in aggregates from 0.50 to <0.25mm in the layer from 0.000 to 0.025m for 0.000 to 0.075m, compared with CT. The largest stock of OLF in the surface layer was observed under NT in the class of the aggregates of 8.00 to 4.76mm. The increases in HF were obtained under the CT. The highest TOC, CGC, CAM, OLF and HF for the CT and NT were found in the classes of larger size aggregates (8.00 to 2.00mm), while a reduction in these stocks declined as the size of aggregates. Through the LIF and the EPR, the humification degree of OM increased with decreased the aggregate classes.